Analisis Faktor-Faktor yang Mempengaruhi Kinerja Pegawai pada Kantor Sekretariat Daerah Kabupaten Kayong Utara - Rafiansyah, Rafiansyah; Puteri, Monika (Jurnal Ilmiah Aset, 2019)
The development and progress of a government agency such as the Office of the Secretariat of the North Kayong Regency area is determined by the Agency in the management’s ability to fulfil the tasks and functions in accordance with the objectives of the organization. For that then the District Secretariat Office of Ketapang in task and function management requires the ability to harness all resources. One element of management or an important resource is human resources. From this fact then the Office of the Secretariat of the Regional District of North Kayong must be able to demonstrate excellence in the face of any changes through good performance. Therefore the Officeof the Secretariat of the North Kayong Regency Areas should pay attention to how keep working to improve his performance. For that then the Office of the Secretariat of the Regional District of North Kayong should first find out what factors can affect the performance of the employee. This research uses research by using descriptive method. Population of 85 employees, samples taken 50% or as much as 43 people Purposive Sampling method with the respondent. Linear regression analysis tool uses multiple. F test can be concluded that the factor rewards, social security, skills, facilities and infrastructure, physical, kepribadiaan, attitude and appreciation in the real effect on performance clerk at the Office of the Secretariat of the North Kayong Regency Area. From the results it can be concluded that the t-test rewards, social security, physical, skills, attitude and appreciation of the real effect on performance. While the factor means/tools and personality partially in this study do not affect real on performance clerk North Kayong Regency Regional Secretariat.